Influence of Screw Spacing on the Strength of Self-Drilling Screw Connection for the High Strength Cold-Formed Steel - Sapiee, Siti Fairuz; Lau, Hieng Ho (Trans Tech Publications, Switzerland, 2013)
Self-drilling screws are the primary means of fastening for cold-formed steel members in cold-formed thin-gauge steel residential construction because it can drill their own holes and form their own threads. The fabrication of connections is the most labour intensive aspect of the cold formed thin-gauge steel construction process, thus a better understanding of the behaviour of screw connections could lead to optimum connection design and reducing the cost of the fabrication. The study carried out to investigate the behaviour of single-shear connections using self-drilling screws in the cold-formed steel construction. The focus of this study is on the influence of the number of screws and screw spacing on the strength of self drilling screw connection. These parameters are varied to determine their influences on the connection strength. The failure load and failure modes were obtained and observed from the tests carried out in the laboratory. Bearing and tilting failures occurred during the testing of these specimens. The predicted connection strengths were calculated using American Iron and Steel Institute (AISI) design equations. A total of 24 specimens of single shear test showed that connection strength is linearly proportional to the number of screw in the connection. Results of the specimen with spacing more than 3d show better correlation with the calculated results as compared to specimens with screw spacing less than 3d.